A Review: Research Trends on Local Wisdom-Based Empathy Values in Science Learning - Muhamad Iksan; Ishak Isa; Jusna Ahmad; Frida Maryati Yusuf; Abubakar Sidik Kaili; Masra Latjompoh (Jurnal Penelitian Pendidikan IPA, 2026)
The integration of empathy values into science education has gained increasing scholarly attention as part of character education and holistic learning paradigms. In multicultural contexts such as Indonesia, local wisdom offers culturally grounded moral frameworks that can strengthen students' socio-emotional competencies, particularly empathy, within science learning. This study aims to synthesize and map global and national research trends on empathy-based local wisdom in science education through a hybrid review approach, combining a Systematic Literature Review (SLR) and bibliometric analysis. A systematic search was conducted across Scopus-indexed journals and SINTA-accredited Indonesian journals published between 2019 and 2025. Following PRISMA guidelines, 21 articles met the inclusion criteria and were analyzed qualitatively to identify conceptual frameworks, instructional models, learning outcomes, and assessment strategies related to empathy development in science education. The results indicate that embedding local wisdom—such as indigenous environmental ethics, communal values, and cultural narratives—into inquiry-based and project-based science learning significantly enhances students' empathy, environmental awareness, and ethical reasoning. However, empirical studies measuring empathy using validated psychometric instruments remain limited, particularly in experimental and longitudinal designs. Furthermore, international publications predominantly emphasize socio-scientific issues, while Indonesian studies focus more on contextual cultural integration. The findings suggest that future research should strengthen interdisciplinary designs, develop standardized empathy assessment tools, and expand cross-cultural comparative studies to advance globally relevant yet locally rooted science education practices.